(untitled) (Proceedings of the International Conference on Education, 2020)
The study deals with the conscious use of the medium "language" in the design of vocational teaching/learning processes in order to make the examination and assessment process of learning outcomes more transparent and appropriate. For this purpose, the study focuses on the use of tasks in written examinations in vocational teaching and in particular on the operators used in these. The question will be investigated as to whether the teaching of operator meanings and the actions required with them leads to an improvement in the results of processing and the understanding of tasks among learners. The theoretical approach is based on the knowledge and action theory of AEBLI (1980; 1981), on the basis of which an instrument is developed for verifying the understanding of tasks. To answer the question, a quasi-experimental intervention study in pretest posttest design with one experimental and control group (n=42) is carried out. For this purpose, the instrument is used to verify the understanding of the tasks in the vocation "educator" at a vocational school. For the development of the treatment, selected operators are conceptually defined, which are frequently used in written final examinations of this profession. The experimental results show that instruction on operators has a significant positive effect on the results of the tasks performed by the learners in the experimental group. This is also obvious for an improved understanding of the learner’s tasks, since here too there are significant positive changes in individual segments of understanding. Finally, conclusions are derived for the development of a mutual understanding of the tasks of teachers and learners as well as for the pedagogical-practical activity of vocational teaching.